THE IMPLEMENTATION OF HUMAN FREEDOM THEORY IN EARLY EDUCATION - Zainal Fadri (State Institute of Islamic Studies Batusangkar, 2021)
Early childhood education is now an obligation to prepare children for further education. Education in primary schools has levels that must be taken first with the aim that the child is ready to attend lessons first, such as education in kindergarten and early childhood education. This study aims to look at human freedom in undergoing early childhood education and the values contained in education. The theory of freedom is used to examine the harmony between the spirit of preparing for education with the pure value of human freedom, so that it can be said that early childhood education is a freedom. The method used in this research is descriptive qualitative. Data analysis was carried out in a holistic manner to achieve an exploration of the theory of freedom contained in early childhood education. The results of this study prove that early childhood education can be said that the implementation of freedom will support the true free human being, that is, free from ignorance and backwardness.